Determination of cytokines for assessment of inflammatory status at genital endometriosis - Appazova, Leila; Akhmaltdinova, Lyudmila; Turdybekova, Yasminur; Kopobayeva, Irina; Amirbekova, Zhanna (Bangladesh Journal of Medical Science, 2024)
Objective: The Aim of the research was to study the profile of serum cytokines in patients with genital endometriosis, as well as to evaluate the sensitivity and specificity of any single cytokine or combination of cytokines in predicting the inflammatory status in endometriosis. Material and methods: The study included 48 patients. They were divided into two groups: I group (experimental) – 28 women with genital endometriosis, II group (control) - 20 healthy non-pregnant women. For the determination of serum biomarkers (IL-6, IL-8, IL-18, TNF-α, MIF) the multiplex immunofluorescence method with XMap technology was used. Results: There were no statistical differences in IL-18 and MIF levels between the studied groups (p = 0.630 and p = 0.421). However, serum levels of IL-6, IL-8, TNF-α were significantly different (respectively, p = 0.037, p < 0.001, p < 0.001). In women with endometriosis the levels of IL-8 and TNF-α were increased 5 times, and level of IL-6 was increased 3 times. The diagnostic significance of IL-6, IL-8 and TNF-α levels for predicting genital endometriosis was 75.0% and 60.0%; 100.0% and 90.0%; 92.9% and 85.0%, respectively. Conclusions: The levels of IL-6, IL-8, and TNF-α were significantly higher in patients with genital endometriosis. The diagnostic significance of IL-6, IL-8 and TNF-α levels for predicting genital endometriosis was also established with the determination of the sensitivity and specificity of the model. Bangladesh Journal of Medical Science Vol. 23 No. 01 January’24 Page : 121-129